Inventarytation of medicinal plants as a self-medication by the Tolaki, Puundoho village, North Kolaka regency, Southeast Sulawesi - Hasria Alang; Hastuti Hastuti; Muhammad Sri Yusal (Universitas Islam Indonesia, 2021)
AbstractBackground: Traditional medicine knowledge is one of the local wisdoms and is passed down from generation to generation. Traditional medicine needs to be preserved in order to maintain the continuity of this knowledge; besides that, it requires a balance between modern medicine and herbal medicine. Herbal medicine is easy to obtain in the surrounding environment, at affordable prices and guarantees the safety of medicinal chemicals that are harmful to the body. The use of drugs for a long period of time is a habit that is harmful to the body organs because they contain certain chemical compounds that are not safe for human vital organs, so it is necessary to make an inventory effort by digging up information from traditional healers. This research is expected to make a significant contribution so that the role of herbal plants can be maintained and developed in the future.Objective: to inventory the plant species which useful as traditional medicines used by traditional healers of the Tolaki tribe in Puundoho village.Method: The method used in this research is a qualitative exploration, through an emic approach or a community and ethical perspective supported by scientific literature. The use of qualitative methods in this study is intended to describe people's knowledgeResults: The interview results with three traditional healers (mbu'wai) in Puundoho village about plants that can be used as traditional medicines. It can be found on the side of the road, garden and yard. The part of the plant used is the whole plant or part of the plant such as roots, stems, or leaves. The method to blend it is boiled or mashed. The use of traditional medicines is applied orally or topically.Conclusion: The types of traditional medicinal plants used by the Tolaki tribe in Puundoho village can be obtained from yards, gardens, and roadsides including sidaguri, ciplukan, jeringan, bangle, purslane, bandotan, boborongan, turi, meniran, banjar berrywit, mesoyi, ketepeng, guava, ginger, kencur, blechnum nails and ketepengKeywords: Herbal medicine, inventarytation, medicinal plants, traditional medicineIntisariLatar belakang: Pengetahuan pengobatan tradisional merupakan salah satu kearifan lokal dan diperoleh secara turun-temurun dari generasi kegenerasi selanjutnya. Pergeseran zaman dan modernisasi dikhawatirkan akan menggerus kearifan lokal tersebut, sehingga perlu dilakukan inventarisasi dengan cara menggali informasi dari para penyehat tradisional. Penelitian ini diharapkan akan memberikan kontribusi yang signifikan, sehingga peran tanaman herbal dapat terus terjaga dan dikembangkan di waktu mendatang.Tujuan: untuk menginventarisasi jenis-jenis tumbuhan yang bermanfaat sebagai obat tradisional yang digunakan oleh penyehat tradisional suku Tolaki di Desa puundoho.Metode: Metode yang digunakan dalam penelitian ini adalah eksplorasi yang bersifat kualitatif, melalui pendekatan emik atau perspektif masyarakat dan etik yang didukung literatur ilmiah. Penggunaan metode kualitatif dalam penelitian ini dimaksudkan untuk mendeskripsikan pengetahuan masyarakatHasil: Hasil wawancara dengan tiga penyehat tradisional (mbu’wai) yang ada di Desa Puundoho tentang tumbuhan yang dapat digunakan sebagai obat tradisional dapat ditemukan di tepi jalan, kebun dan pekarangan. Bagian tanaman yang digunakan adalah keseluruhan bagian tanaman atau sebagian tanaman seperti akar, batang atau daun. Cara meramunya yaitu direbus atau dihaluskan. penggunaan obat tradisional tersebut dilakukan secara cara oral atau topical.Kesimpulan: jenis tanaman obat tradisional yang digunakan oleh suku Tolaki di desa Puundoho dapat diperoleh dari pekarangan, kebun, dan pinggir jalan diantaranya sidaguri, ciplukan, jeringan, bangle, krokot, bandotan, boborongan, turi, meniran, rumput beriwit banjar, mesoyi, ketepeng, jambu air, jahe, kencur, paku blechnum dan ketepeng